CAPITAL STRUCTURE OF INDONESIAN BANKING FIRMS: THE EFFECTIVENESS OF INDEPENDENT COMMISSIONERS - Rega Dwi Cahyani; Maulida Nurul Innayah; Wida Purwidianti; Yudhistira Pradhipta Aryoko (COMPETITIVE, 2025)
This study aims to analyse the effect of family ownership proxied by political connections on capital structure with independent commissioners as a moderating variable in banking companies listed on the Indonesia Stock Exchange from 2018 to 2022. The sampling technique used is purposive sampling, which produces 140 observations. The data analysis technique used is panel data regression model analysis using Stata 17. The results of the preliminary test show that this study uses a fixed effect model. The results of this study found that family ownership has a negative and significant effect on capital structure. In addition, this study found that political connections and independent commissioners have a positive and significant effect on capital structure. Furthermore, the results of the moderation test show that independent commissioners strengthen the negative effect of family ownership and weaken the positive effect of political connections on capital structure. Based on the results of this study, banking companies in Indonesia need to pay attention to political connections and independent commissioners because they have been proven to increase the proportion of company debt, which is considered to reduce agency problems according to agency theory and resource-based theory.